Investigation on CO2 absorption and compressive strength of paver blocks incorporating seaweeds and potato peels. (2022) - Revathi, S.; Suganya, R.; Haamidh, A.
Abstract: The challenge that we face in our daily life is the increasing amount of emissions of CO2 which has led to the increased concentration in the atmosphere that results in global warming. The global warming occurs mainly due to the emission of greenhouse gases in the atmosphere. Out of the emitted greenhouse gases, CO2 counts for 72%, 18% counts for methane and 9% counts for nitrous oxide (NOX ). From this it is very clear that CO2 emission is the major area of concern for global warming. The CO2 emission occurs due to the incomplete combustion occurring in the vehicle engines that involve fuels like oil, natural gas, diesel, organic-diesel, petrol, organic-petrol and ethanol. The emission rate of CO2 keeps increasing on daily basis and to put this under control, CO2 absorbing paver blocks had been casted which includes the addition of lime, potassium hydroxide, seaweeds and potato peels. By using the above mentioned materials, four different types of paver blocks were casted. The first type composition had been carried out by using 0.5% lime and 5% weight of cement. The second type composition had been carried out by using 0.5% potassium hydroxide and 5% weight of cement. The third type composition had been carried out by using 0.5% seaweeds and 5% of weight of cement. The fourth type composition had been carried out by using 0.5% seaweeds and potato peels and 5% weight of cement and finally control specimens were casted. The mix proportion was adopted by using M35 as it is the suggested grade for mild traffic. The Carbonation tests were carried out by employing two methods such as carbonation test and titration method. In the carbonation test, the paver block was placed in normal atmosphere and testing was carried out on the 7th day, 14th day and 28th day using phenolphthalein indicator. The Titration method was carried out for all the four types of paver blocks by using sodium hydroxide and HCL. The compressive strength had been tested for all the four types paver block on the 7th, 14th and 28th day. The experimental results obtained reveals that the paver block casted by using the addition of seaweeds and potato peels in the combination of 5% by weight of cement had absorbed more amount of carbon dioxide and the compressive strength of this specimen is equal to the compressive strength of the conventional specimen.